Career progression and formal versus on-the-job training - Jerome Adda; Christian Dustmann; Costas Meghir; Jean-Marc Robin (Institute for Fiscal Studies (IFS), 2010)
We evaluate the German apprenticeship system, which combines on-the-job training with classroom teaching, by modelling individual careers from the choice to join such a scheme and followed by their employment, job to job transitions and wages over the lifecycle. Our data is drawn from administrative records that report accurately job transitions and pay. We find that apprenticeships increase wages, and change wage profiles with more growth upfront, while wages in the non-apprenticeship sector grow at a lower rate but for longer. Non-apprentices face a much higher variance to the shocks of their match specific effects and a substantially larger variance in initial level of the offered wages. We find no evidence that qualified apprentices are harder to reallocate following job loss. The average life-cycle return to an apprenticeship career is about 14% and the return is mainly driven by the differences in the wage profile.
Keywords: 330; Apprenticeship Training; Job Mobility; Labour Supply; Wages; Wage determination; Matching; Wage Growth; Dynamic Discrete Choice; In-work Benefits; EITC; Education; Arbeitsmarkt; Arbeitsmobilität; Betriebliche Ausbildung; Berufsbegleitende Ausbildung; Arbeitslosenversicherung; Einkommensteuerrecht; Wirtschaftsmodell